Poland syndrome with associated synbrachydactyly and dextrocardia: a rare case - Rajawat, Govind Singh; Khippal, Narendra; Takhar, Rajendra Prasad (International Journal of Research in Medical Sciences, 2018)
Poland’s Syndrome is a rare congenital condition. It is classically characterized by absence of unilateral chest wall muscles and sometimes ipsilateral symbrachydactyly (abnormally short and webbed fingers). The condition typically presents with unilateral absence of the sternal or a breast portion of the pectoralis major muscle which may or may not be associated with the absence of nearby musculoskeletal structures. Authors report a 13-year-old male patient with typical features of Poland syndrome associated with synbrachydactyly and dextrocardia. This association is very rare, till 2010, only 19 cases have been described in scientific literature (Poland syndrome with dextrocardia), in this case synbrachydactyly also associated on ipsilateral side. To the best of our knowledge, this is the first documented case of the left sided Poland syndrome with dextrocardia and symbrachydactyly reported from the South East Asia Region (SEAR).